Numerical evaluation of grasslands dominated by Sesleria juncifolia agg. in Serbia - Kabaš, Eva; Vukojičić, Snežana; Alegro, Antun; Surina, Boštjan; Kuzmanović, Nevena; Šegota, Vedran; Lakušić, Dmitar (Hacquetia, 2015)
Phytosociological and numerical analyses of grasslands dominated by Sesleria juncifolia s.l. in Serbia were performed in order to resolve their syntaxonomy and nomenclature. Twelve relevés were sampled on Mt. Mučanj (western Serbia), which were then compared with similar relevés from other parts of the Balkan Peninsula by means of numerical analyses. The relevés were classified using cluster analysis, while the ordination was conducted using Detrended Correspondence Analysis (DCA). The results suggest the occurrence of two floristically well defined Dinaric associations in Serbia: Seslerio juncifoliae-Edraianthetum graminifolii ass. nova from Mt. Mokra Gora (Oxytropidion urumovii, Elyno-Seslerietea) and Diantho petraeae-Seslerietum juncifoliae ass. nova (Chrysopogono-Saturejion, Festuco-Brometea) from Mt. Mučanj.